APPLICATION OF 2D SURFACE ELECTRICAL RESISTIVITY TOMOGRAPHY TO DETECT THE UNDERGROUND CAVITIES A CASE SITE STUDY: TOLGA AREA (ALGERIA) - HEBBACHE, K; MELLAS, M; BOUBAYA, D (Courrier du Savoir; Vol. 21 (2016): COURRIER DU SAVOIR (NOVEMBRE), 2016)
Electrical resistivity tomography method is considered among the best non-destructive and non invasive geophysical techniques for detecting and characterizing the underground cavities and associated disorders. The detection of cavities in urban areas is important to prevent against different causes of accidents related to possible collapse and subsidence. This study focused on the application of electrical resistivity measurements to locate and identify cavities in the soil. The survey site is located in Biskra City, south-east of Algeria. This field contains cavities of natural origin and different sizes. The procedure using the electrical resistivity tomography of Wenner array permitted to detect the cavities in the range of depth 2 to 4m. These cavities were caused by the dissolution phenomena of carbonate materials. Also mechanical and dynamic penetrometer tests were performed in order to propose a solution for foundations building.